Secure Data Sharing Mechanism in Cloud Computing With Keyword Search Base ABE Algorithm - Shaik Riyaz; S. Noortaj (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Attribute-Based Proxy Re-Encryption schemes are designed to make secure data sharing possible based on user attributes, all without the need for a centralized authority to handle encryption or re-encryption. However, many of these ABPRE models fall short when it comes to supporting efficient keyword searches and dynamic keyword updates, often relying on a Private Key Generator. To address this gap, Ge et al. introduced the CPAB-KSDS scheme, which is a cipher text-policy ABPRE framework that allows for secure keyword searches and updates without needing PKG involvement. They claim that CPAB-KSDS maintains indistinguishability against chosen-cipher text attacks and chosen-keyword attacks within the random oracle model. In our review of Ge et al.’s CPAB-KSDS scheme, we’ve identified some major weaknesses in how they reduce security from IND-CKA to the foundational assumptions. Additionally, we’ve outlined a particular attack that undermines the IND-CKA security of CPAB-KSDS. Our research indicates that CPAB-KSDS falls short of the IND-CKA security it purports to offer, exposing critical vulnerabilities in encryption schemes that incorporate keyword search and update features.